A COMPREHENSIVE REVIEW ON DIFFERENT TECHNIQUES OF IMAGE FUSION (International Journal of Engineering and Computer Science, 2014)
Image fusion is one of the current areas of research of image processing. Image fusion is the process of combining two or more images or some of their features into a single image retaining the features from each of the original images without the introduction of distortion or loss of information. The fusion of images is often required to integrate complementary multisensor, multitemporal and/or multiview information into one new better quality image. In this paper we will discuss the different levels and techniques of image fusion. This Paper will be helpful for the research in the field of image fusion